2004
DOI: 10.1007/bf03033294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes associated with DISC1, a candidate gene for schizophrenia

Abstract: Genetic factors play an important part in the development of schizophrenia and bipolar disorder, and linkage analyses in families have successfully identified several chromosomal regions containing candidate genes. A single large pedigree has been described in which schizophrenia and depression segregate with a balanced chromosomal translocation involving the long arm of chromosome 1 and the short arm of chromosome 11. The gene named DISC1, disrupted at the chromosome 1 breakpoint, is a novel candidate gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Our findings parallel the phenotypical heterogeneity of familial DISC1 cases in the original Scottish pedigree (St Clair et al, 1990;Blackwood et al, 2001;Blackwood and Muir, 2004). We find it remarkable that a single mutation can result in such diverse phenotypes as schizophrenia, bipolar disorder, and recurrent depression.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings parallel the phenotypical heterogeneity of familial DISC1 cases in the original Scottish pedigree (St Clair et al, 1990;Blackwood et al, 2001;Blackwood and Muir, 2004). We find it remarkable that a single mutation can result in such diverse phenotypes as schizophrenia, bipolar disorder, and recurrent depression.…”
Section: Discussionsupporting
confidence: 79%
“…Patients from the Scottish pedigree are heterozygous for the DISC1 mutation, and given the high penetrance of the phenotype (Blackwood et al, 2001;Blackwood and Muir, 2004), it seems that a loss of 50% of the gene dose is pathogenic (by haploinsufficiency). However, no data have been reported on DISC expression levels in these patients, and compensatory mechanisms may increase gene expression of the healthy allele.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of BICD1 with EEG variability is further suggested because BICD1 interacts directly with LIS1 (37), a protein that also interacts directly with DISC1 (38). Variation at DISC1 has been associated with alteration in the P300-evoked potential, another phenotype of neuronal reactivity (39).…”
Section: Discussionmentioning
confidence: 99%
“…Linkage with schizophrenia alone is also significant, producing an LOD score of 3.6. 2 Blackwood et al 2,3 further reported that the psychiatric presentations are typical with no other distinguishing clinical features. They also reported that, in unaffected translocation carriers, the latency and amplitude of the event related potential (ERP) P300, a measure of the speed and efficiency of information processing, is indistinguishable from that of affected individuals.…”
Section: Genetics Of Disc1 Discoverymentioning
confidence: 99%